Recently amplified arctic warming has contributed to a continual global warming trend. Issue 12 (December 2017) - Huang, Jianbin; Zhang, Xiangdong; Zhang, Qiyi; Lin, Yanluan; Hao, Mingju; Luo, Yong; Zhao, Zongci; Yao, Yao; Chen, Xin; Wang, Lei; Nie, Suping; Yin, Yizhou; et al.
Abstract The existence and magnitude of the recently suggested global warming hiatus, or slowdown, have been strongly debated1–3 . Although various physical processes4–8 have been examined to elucidate this phenomenon, the accuracy and completeness of observational data that comprise global average surface air temperature (SAT) datasets is a concern9, 10 . In particular, these datasets lack either complete geographic coverage or in situ observations over the Arctic, owing to the sparse observational network in this area9 . As a consequence, the contribution of Arctic warming to global SAT changes may have been underestimated, leading to an uncertainty in the hiatus debate. Here, we constructed a new Arctic SAT dataset using the most recently updated global SATs2 and a drifting buoys based Arctic SAT dataset11 through employing the 'data interpolating empirical orthogonal functions' method12 . Our estimate of global SAT rate of increase is around 0.112 °C per decade, instead of 0.05 °C per decade from IPCC AR51, for 1998–2012. Analysis of this dataset shows that the amplified Arctic warming over the past decade has significantly contributed to a continual global warming trend, rather than a hiatus or slowdown. The Arctic is under-represented in surface temperature datasets and this could affect estimates of global warming. A new dataset with greater coverage of the Arctic shows a higher warming rate of 0.112 °C per decade compared to 0.005 °C from IPCC AR5.